10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Falls are a significant cause of morbidity in idiopathic normal pressure hydrocephalus (iNPH), yet the specific motor domains driving fall occurrence and fall frequency remain uncharacterized. OBJECTIVES: The aim is to identify specific motor profiles associated with fall occurrence versus fall frequency in iNPH, and to evaluate relationships between cerebrospinal fluid (CSF) drainage trial responsiveness and shunt surgery outcomes. METHODS: We retrospectively analyzed 323 patients with possible or probable iNPH. Fall history and multi-domain motor assessments (gait speed, endurance, and balance) were evaluated pre- and post-CSF drainage. Multivariable regression assessed domain-specific fall risk and continuous factors correlating with post-surgical gait improvement in shunted patients (n = 117). RESULTS: Greater endurance and leg strength independently predicted a lower likelihood of experiencing any fall (P < 0.05). Conversely, a higher frequency of recurrent falls was associated with broader motor deterioration, including slower dynamic mobility and reduced static balance (P < 0.001). Regarding surgical outcomes, greater baseline severity and drainage trial responsiveness in dynamic speed tests independently correlated with the magnitude of long-term post-surgical recovery (P < 0.05). CONCLUSIONS: A functional dissociation exists in the iNPH motor presentation which is that fall occurrence links to strength and endurance deficits, whereas a higher number of falls is driven by degraded complex balance. Multi-domain assessments effectively stratify patient-specific fall risk, whereas dynamic speed best correlates with surgical recovery.